Dissemination and Contestation of Kyai’s Religious Discourse in Digital Spaces and Its Impact on Followers - Muhamad Maimun; Syaifuddin Zuhri; Zaenal Arifin; Babun Suharto (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This study examines the transformation of Kyai leadership within the pesantren tradition amid the rising influence of digital media, using the controversy surrounding Trans7’s Xpose Uncensored episode on Pesantren Lirboyo as a critical case. this research analyzes how Kyai leadership is constructed, contested, and recontextualized in the era of viral media. Findings reveal four key transformations. First, despite media pressure, Kyai authority in Lirboyo remains anchored in charismatic moral–spiritual leadership while adapting to media logic through ethical and calm communicative strategies, consistent with Hjarvard’s (2008) theory of the mediatization of religion. Overall, this study demonstrates that the leadership of Kyai in the digital era is simultaneously charismatic, adaptive, and dialogical, reflecting a harmonious integration of pesantren tradition with contemporary media culture. The Lirboyo case serves as evidence that religious authority in Indonesia is undergoing significant transformation, not through erosion, but through strategic negotiation within the logic of viral digital communication.